POLYMER-BASED IONIC CONDUCTORS - Mohd Arof, Abdul Kariem (Malaysian Journal of Science, 2023)
Polymer electrolytes consist of polymer matrices with ion transport capabilities and can exist in either a solid or gel state. In both states, the incorporation of plasticizers and fillers will improve the ionic conductivity. Gel polymer electrolytes (GPEs) exhibit ionic conductivity levels remarkably akin to those of liquid electrolytes, owing to the direct solvation of salts within solid polymer electrolytes.